What Do We Know about Spondylodiscitis in Children? A Retrospective Study - Ayla Yagdiran; Charlotte Meyer-Schwickerath; Raphael Wolpers; Christina Otto-Lambertz; Katrin Mehler; Andre Oberthür; Nikolaus Kernich; Peer Eysel; Norma Jung; Kourosh Zarghooni (MDPI AG, 2022)
Pediatric spondylodiscitis (PSD) is a rare disease with a major impact on mobility and functional status. Data concerning demographic and microbiological characteristics, clinical course, treatment, and outcome are scarce. Therefore, the aim of this study was to present clinical experiences of a third-level hospital (2009-2019) in PSD and compare these with adult spondylodiscitis (ASD). Of a total of 10 PSD patients, most of the infants presented with unspecific pain such as hip pain or a limping, misleading an adequate diagnosis of spine origin. Eight patients could be treated conservatively whereas surgery was performed in two cases with one case of tuberculous PSD (tPSD). The causative agent was detected in three of the patients. The diagnosis of PSD is often difficult since clinical symptoms are unspecific and causative pathogens often remain undetected. Nevertheless, empirical anti-infective therapy also seems to be effective. Based on recent studies, clinicians should be encouraged to keep the duration of anti-infective therapy in children short. Since comorbidities are not presented in PSD it is unclear which children suffer from PSD; thus, studies are necessary to identify predisposing factors for PSD. In our study, PSD differs from ASD in diagnostic and especially in therapeutic aspects. Therefore, specific guidelines for PSD would be desirable.